ERYTHROCYTE GLUCOSE-6-PHOSPHATE DEHYDROGENASE DEFICIENCY AS A CAUSE OF NEONATAL JAUNDICE (The Research of Medical Science Review, 2025)
Background: Neonatal jaundice is the One of the leading causes of hemolytic jaundice in newborns, especially when prevalent among a population, is glucose-6-phosphate dehydrogenase (G6PD) deficiency. Objectives: To find the erythrocyte G6PD deficiency is found in neonates with jaundice and see if it plays a role in the condition. Study Design : A Descriptive observational study Place and Duration of study. From 04 September 2024 to 03 March 2025 Paediatrics Department Balochistan Institute of Child Health & Services Quetta. Balochistan Methods: 100 newborns who had clinically diagnosed jaundice and were treated at a tertiary care hospital. The G6PD enzyme function was measured by using spectrophotometric techniques. Clinical and laboratory findings were studied to check if G6PD deficiency relates to the severity of jaundice. Analyses were conducted using SPSS 24.0. Results: 100 babies selected was 5.6 days. One quarter of the cases were found to have G6PD deficiency. The bilirubin level in the serum of deficient newborns (18.2 ± 3.4 mg/dL) was significantly higher than that of non-deficient infants (13.6 ± 2.8 mg/dL) (p < 0.001). Newborns deficient in G6PD received greater phototherapy and stayed in the hospital longer than other babies. Conclusion: Many cases of neonatal jaundice in our population are due to erythrocyte G6PD deficiency. It is important to catch lung cancer early so treatment and prevention of complications can begin promptly.